2020
DOI: 10.3389/fneur.2020.00026
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Enlargement and the Risk of Stroke: A Meta-Analysis of Prospective Cohort Studies

Abstract: Background: The association between left atrial size and the risk of stroke has not been fully understood. We performed a meta-analysis of prospective cohort studies to determine whether left atrial enlargement (LAE) is associated with an increased risk of stroke. Methods: We searched PubMed, EMBASE, Web of Science, and the Cochrane Library through May 2019. Prospective cohort studies were included if they reported hazard ratios (HRs) and corresponding 95% confidence intervals (CIs) of stroke with respect to L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…First, we were able to replicate previous observations demonstrating associations between greater LA volume and cardiovascular diseases [7][8][9][10]19,20 . Participants with a history of AF had larger LA volumes; and participants with larger LA volumes were more likely to be subsequently diagnosed with AF, stroke, or heart failure.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…First, we were able to replicate previous observations demonstrating associations between greater LA volume and cardiovascular diseases [7][8][9][10]19,20 . Participants with a history of AF had larger LA volumes; and participants with larger LA volumes were more likely to be subsequently diagnosed with AF, stroke, or heart failure.…”
Section: Discussionsupporting
confidence: 74%
“…Enlargement of left atrial (LA) volumes is commonly observed with hypertension 7 , heart failure 8 , or after a diagnosis of AF 9,10 -and AF plays a causal role in this process 11 . Enlargement of the LA and decreased LA function have also been identified as independent risk factors for AF 10,[12][13][14][15][16][17] and stroke [18][19][20] . Together these atrial structural, contractile, or electrophysiological changes that have clinical consequences have been termed atrial cardiomyopathies 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…We defined the cutoff value of LA enlargement as LA diameter more than 50 mm, as LA diameter more than 50 mm had been previously reported to be associated with a higher risk of stroke and systemic embolization in patients with AF ( 11 ). Besides, in our study the LA size was not controlled for body size because it did not significantly affect the results and it has been reported that LA size not controlled for body size was associated with an increased risk of stroke in patients with AF ( 17 ).…”
Section: Methodsmentioning
confidence: 85%
“… 26 A recent systematic review involving six cohorts concluded that LAE was related to an increased and graded risk of stroke independent of age, sex, hypertension and diabetes. 2 In our study, when LAD was dichotomised based on sex-specific partition values, subjects with LAE exhibited elevated incident rates of stroke and its mortality in the overall and stratified comparisons. The Kaplan-Meier curves revealed that LAE was significantly associated with higher stroke incidence in male, female and ischaemic subtype, as well as worse stroke-free survival in male and ischaemic stroke.…”
Section: Discussionmentioning
confidence: 64%